Cardiac failure in a child with tuberculous meningitis as a complication of Paroxysmal sympathetic hyperactivity - Özkaya, Pınar Yazıcı; Turanlı, Eşe Eda; Arı, Hatice Feray; Kurt, Serap; Karapınar, Bülent (The Turkish Journal of Pediatrics, 2022)
Background. Paroxysmal sympathetic hyperactivity (PSH) is a disorder due to the loss of regulation of autonomic activity. The most common condition predisposing to the development of PSH is traumatic brain injury (TBI), followed by anoxic brain injury, stroke, tumors, and infections. Awareness about the condition and early recognition is important to avoid life threatening complications. Case. We report a 4-year-old child with tuberculous meningitis with symptoms of PSH who developed cardiac failure. PSH episodes were treated with beta blocker, benzodiazepine, morphine, dexmedetomidine, baclofen, and tizanidine. Three weeks after readmission PSH episodes decreased and the patient was transferred to the general ward. Conclusions. PSH assessment tool has benefits such as monitoring the patient, evaluating response to treatment and early diagnosing PSH patients.
Keywords: child; paroxysmal sympathetic hyperactivity; tuberculous meningitis